Sistem Politik Indonesia Pasca Reformasi - Endang Komara (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
This article was written with the purpose to provide analysis of the Indonesian political system after the reform. As we know that the political system is often regarded as the allocation of values ​​developed in the midst of society and every citizen appreciate them as ways of life. Appreciation of the value in the middle of the community is an achievement that fought to be obtained. Efforts made by doing internal intergenerational mobility of the political community to achieve the degree of political stability. Post-reform, the political system for the better, in which the role of the people more real in terms of repositioning the political system, from the selection of members of DPR / DPRD, DPD member elections, up to the local elections directly. The distribution of power is already at a level that means, it’s just that people in the region do not yet have the ability to understand that the distribution of power is an opportunity to develop the region. In contrast, the distribution of power in the area it gave birth to the corrupt spirit ingrained in people’s lives. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2814